Possibilities of using intestinal microflora transplantation in the treatment of gastrointestinal diseases - Krawiec, Karol; Sławiński, Aleksander; Ryczkowski, Aleksander; Neścior, Małgorzata; Toruń, Zuzanna; Orzeł, Anna; Majchrzak, Aleksandra; Piech, Piotr (Journal of Education, Health and Sport, 2018)
The number of Clostridium difficile infections (CDI) has significantly increased in Poland and throughout Europe. Their treatment involves the administration of metronidazole, vancomycin or fidaxomicin as indicated in current recommendations. Despite proper approach to the treatment, numerous recurrences of Clostridium difficile are reported. Fecal microflora transplant (FMT) is an alternative yet effective method of treatment of CDI. Moreover, this method is increasingly implemented in other disease entities. DESCRIPTION OF THE PROBLEM: Fecal microflora transplant (FMT) is a safe method of treating intestinal dysbiosis. The therapy is based on transferring the stool suspension from a healthy human (donor) to the patient (recipient). The transplant can be performed by oral route (through the gastric/duodenal probe) or via the rectal route (colonoscopy). The donor of the FMT material must give an informed consent to have performed numerous blood and stool tests that are included in the donor selection procedures. The day before transplant, the recipient has to take the last dose of vancomycin taken in the 14-day treatment.